In vitro anti-cancer activity comparison of the freeze-dried and spray-dried bromelain from pineapple stems - Worapaka Manosroi (2018)
© 2017, Chiang Mai University. All rights reserved. Bromelain is one of the proteolytic enzymes found in pineapple stems and fruits. It has been investigated for medical uses including anti-cancer activity. The objective of this study was to compare the in vitro anti-cancer activities of the freeze-dried and spray-dried bromelain from pineapple stems. Bromelain was precipitated from the pineapple stem juice by 95%v/v ethanol and then freeze-dried or spray-dried to get the dry powder. Both bromelain samples were investigated for anti-cancer activities including anti-proliferative by sulforhodamine B (SRB) assay and apoptotic induction by acridine orange (AO) and ethidium bromide (EB) double staining on seven human cancer cell lines. The highest anti-proliferation of the freeze-dried and the spray-dried bromelain was observed on A549 with the IC 50 values of 18.31±5.11 and 26.36±9.76 μg/ml, respectively. For apoptotic induction, the highest activity of the freeze-dried and the spray-dried bromelain was observed on KB (7.53±3.51%) and A549 (6.29±0.28%) cell lines, respectively. The freeze-dried and the spray-dried stem bromelain exhibited higher immunostimulating activity of the bromelain samples performed in murine neutrophils using nitroblue tetrazolium (NBT) dye reduction test than the negative control of 4.37 and 4.40 times, respectively. This study has demonstrated not only the no significant different effect of the drying processes on the anti-cancer activities of the stem bromelain in seven cancer cell lines, but also the potential of the stem bromelain to be developed as an active compound for lung cancer because of its highest anti-proliferation and apoptosis induction in A549.